2005
DOI: 10.1002/pca.852
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of vinca alkaloids by direct-injection electrospray ionisation tandem mass spectrometry and confirmation by high-performance liquid chromatography-mass spectrometry

Abstract: A simple and rapid method for the identification of Vinca alkaloids from a crude extract of Catharanthus roseus G. Don (Apocynaceae) by direct-injection electrospray ionisation (ESI) and tandem mass spectrometry (MS/MS) has been developed. The alkaloids vindoline, vindolidine, vincristine and vinblastine were evaluated in a commercial extract of C. roseus using this method. Catharanthine and its isomers 19S-vindolinine and vindolinine were detected in the commercial product by direct injection ESI/MS/MS and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…19 The fragment ion of 305 at m/z 337 may suggest the existence of tabersonine, and the fragment ion of 321 at m/z 353 may suggest the existence of an isomer of ajmalicine. 20 These results confirm that C20hi cells have the ability to produce vindoline and catharanthine.…”
Section: Alkaloids In C20hi Detected By Hplc/esi-ms 2 After Light Andmentioning
confidence: 99%
“…19 The fragment ion of 305 at m/z 337 may suggest the existence of tabersonine, and the fragment ion of 321 at m/z 353 may suggest the existence of an isomer of ajmalicine. 20 These results confirm that C20hi cells have the ability to produce vindoline and catharanthine.…”
Section: Alkaloids In C20hi Detected By Hplc/esi-ms 2 After Light Andmentioning
confidence: 99%
“…These ions were probably produced by other isomeric compounds of catharanthine like vindolinine and tabersonine, both having the same molecular mass of 336. Zhou et al [12] have also shown that direct-injection ESI-MS/MS not only gives important information on the molecular masses of catharanthus alkaloids but also provides characteristic structural information that is useful in identifying the compounds. …”
Section: % Ctr % Vdlmentioning
confidence: 99%
“…High performance liquid chromatography-electrospray ionization-mass spectrometry (HPLC-ESI-MS) provides a highly selective and sensitive means for identification of the alkaloids [10,11]. Direct-injection ESI-MS has also been used for rapid identification of Catharanthus alkaloids [12]. In this work compounds from the reaction mixture were analyzed and identified using HPLC-UV and the identification was confirmed by direct-injection ESI-MS/MS in positive ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…Hörhammericine and tabersonine can be detected at 329 nm. The protocol was adapted from Zhou et al (2005) [1]. For 40 minutes, at a flow rate of 0.8 ml/min, the mobile phase was linearly ramped from a 45:55 to a 65:35 mixture of methanol:0.1% triethylamine.…”
Section: Hplc Analysis Of Metabolitesmentioning
confidence: 99%